Representasi Karya Instalasi Nia Gautama “The Raped Love” Dalam Seni Rupa Kontemporer - Ramadhani, Novia Dwi; Sujana, Anis; Nagara, Martien Roos (ATRAT: Jurnal Seni Rupa, 2024)
This study examines the installation artwork “The Raped Love” by Nia Gautama, which addresses issues of women, trauma, and recovery. With a background in contemporary art as a medium for conveying social messages, this research employs a qualitative method with Roland Barthes’ semiotic approach to analyze signs and symbols within the artwork. The research questions encompass how Nia Gautama represents women’s issues, the meanings of symbols and visual elements in this work, as well as the exploration of themes of female identity, courage, and resilience. The research aims to analyze the visual and narrative aspects of the artwork, understand the symbolism in the context of women’s representation and feminism, and explore themes of female identity, courage, and trauma recovery. The findings indicate that “The Raped Love” effectively utilizes symbolism to convey the complexity of women’s experiences and offers a new discourse on courage and recovery.